High school students' perceptions of using social media in learning English: A quantitative study - Ayudia Fauziah; Djoko Sutrisno (Universitas Ahmad Dahlan, 2024)
The main aim of this research is to investigate how secondary school students understand the usefulness of social media in English language learning. The research design used in this research is quantitative research, and data was collected through closed surveys and given to 31 students from SMKN 1 Bantul, Yogyakarta. The questionnaire contains 18 items representing the cognitive, affective, and conative dimensions of social media use in ELT. Based on these findings, students generally have a positive attitude toward using social media to learn English. By providing interesting and easily accessible content, social media is useful in improving students' English skills. Listening and reading skills can be significantly improved by using platforms such as YouTube, Instagram, and TikTok. These results suggest that the diverse sources of stimulation and conducive interactive contextual practices offered by social media support learners' needs while presenting challenges with exposure to non-standard language or distractions that may occur during its use.